2018
DOI: 10.1111/vcp.12573
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 3 resuscitative fluid therapies on hemostasis as measured by rotational thromboelastometry in dogs

Abstract: Clinically relevant doses of resuscitative fluids resulted in a decreased clot firmness in the intrinsic pathway, as measured by TEM, which affected hemostatic variables in healthy dogs. There was also a significant individual response to treatment. The changes noted in this study are not expected to result in clinically apparent bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Changes reported were not associated with clinical signs, but the population included healthy dogs, and identification of bleeding tendency was not the aim of the study. 12,41,42 In the HS-treated group, several ROTEM parameters were different between T0 and T1, with a tendency toward hypocoagulability, and a decrease in MCE PLT was indicative of reduced platelet contribution to clot contraction/elasticity. Although no difference was reported at T1 for the MCE PLT between the 2 groups, further studies with an increase in sample size or with different amounts of solutions administered could help to clarify this result.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Changes reported were not associated with clinical signs, but the population included healthy dogs, and identification of bleeding tendency was not the aim of the study. 12,41,42 In the HS-treated group, several ROTEM parameters were different between T0 and T1, with a tendency toward hypocoagulability, and a decrease in MCE PLT was indicative of reduced platelet contribution to clot contraction/elasticity. Although no difference was reported at T1 for the MCE PLT between the 2 groups, further studies with an increase in sample size or with different amounts of solutions administered could help to clarify this result.…”
Section: Discussionmentioning
confidence: 97%
“…Similar results on the standard coagulation profile were observed by Seshia et al after administration of 5 mL/kg of HS over 15 minutes and 20 mL/kg of HES over 30 minutes in healthy dogs, making it more likely that these changes were due to HS administration and not exclusive to our population. 42 After HS bolus administration, sodium and chloride were increased, to consumption of clotting factors and platelets caused by DIC. 31,33 One abstract published to date has described the use of a viscoelastic technique (TEG) in dogs with GDV, reporting that dogs with baseline TEG values outside the reference range had higher mortality than dogs without abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in contrast to the studies by Bochsen, McMichael, Smith, Nagler and McMichael. An in vivo study that assessed the effect of clinically relevant doses of resuscitative fluids in dogs, using TEM, found that maximum clot firmness decreased after treatment with all fluid types, possibly the result of a dilutional effect on platelets and fibrinogen (Seshia et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%